Frames and framing effects in Chinese online and offline crisis communication: the case study of a celebrity scandal. Issue 3 (3rd July 2018) - Wu, Fang; Choy, Christine Hiu Ying
Abstract : This study develops a model for analyzing the flow of frames and the multiple levels of framing effects in Chinese crisis communication both online and offline. To investigate the convergence and/or divergence of traditional media and social media in framing a crisis event in China, the study uses the sample of a celebrity scandal case that received extensive attention both online and offline. The empirical findings showed that crisis communicative strategies (CCSs), that is, the frames used in crisis communication, were correlated with those used in newspaper coverage (i.e. frames in representation) but were not correlated with the CCSs used by the online public (i.e. frames in thoughts). Specific and defensive CCSs, such as attacking the accusers and denial, led to fewer favorable responsibility-oriented frames than ambiguous strategies, such as excuses and justification. This finding supports the assumptions of classic situational crisis communication theory. However, none of the above-mentioned CCSs significantly predicted the relationship-oriented frames in thoughts. Relationship-oriented frames were found to be a predictor of the valence of online public opinion whereas no CCS was observed to be influential in the online public opinions expressed by social media users.